Elevated red blood cell folate levels are associated with metabolic dysfunction-associated steatotic liver disease: results from NHANES 2017–2020 - Liao, Xin; Yu, Song; Wang, Lin; Zhang, Ruyue; Yu, Ke (Frontiers in Physiology, 2025)
IntroductionMetabolic dysfunction-associated steatotic liver disease (MASLD) is the most prevalent chronic liver disease worldwide. However, the role of folate in MASLD remains controversial. This study aimed to investigate the association between two folate indicators [serum folate and red blood cell (RBC) folate] and MASLD prevalence using data from the 2017–2020 National Health and Nutrition Examination Survey (NHANES).MethodsA total of 3,879 participants without liver disease or significant alcohol consumption were included in the final analysis. Hepatic steatosis was assessed via transient elastography, with MASLD defined as a controlled attenuation parameter (CAP) ≥285 dB/m and the presence of at least one cardiometabolic risk factor. Logistic regression and generalized additive models (GAMs) were used to evaluate associations between folate levels and MASLD, with subgroup analyses stratified by age, gender, and body mass index (BMI).ResultsAfter full adjustment for confounders, RBC folate exhibited a significant positive association with MASLD (OR = 1.111 and 95% CI: 1.015–1.216 per 1-unit increase). In contrast, serum folate showed a transient negative association in minimally adjusted models (OR = 0.869 and 95% CI: 0.802–0.941), which disappeared after further adjustments. Subgroup analyses confirmed that age, gender, and BMI did not modify the RBC folate–MASLD relationship.DiscussionThese findings suggest that elevated RBC folate levels are independently associated with MASLD prevalence, whereas serum folate may lack clinical relevance due to susceptibility to confounding factors. RBC folate, as a stable biomarker of long-term folate status, may serve as a superior indicator for investigating folate–MASLD associations.